Congenital Circumferential Constriction Band of the Abdomen: A Case Report. (8th February 2010) - Gargh, Kapil; Sullivan, Carol; Laing, Hamish; Banerjee, Sujoy
Abstract : We report a case of congenital constriction band of abdomen associated with limb pseudarthrosis. The constriction band around the abdomen, though may cause initial difficulty with ventilation and parental distress, does not interfere with feeding, bowel movements, and growth. It heals spontaneously with supportive treatment though surgery may be needed in some cases.